MENGUBAH PROFESI, MENGUBAH DUNIA : Yesus Memanggil Murid-MuridNya yang pertama (Mat. 4:18-22) - Edwar Adelbert Mere (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This study analyzes the text of Matthew 4:18–22 regarding the calling of the first disciples at the Sea of Galilee as a crucial moment in the formation of Jesus' mission community. The purpose of this writing is to explore deep meaning through textual, narrative, and various multidimensional approaches to find theological relevance for contemporary life. Textually, the emphasis is placed on the use of the term